2017
DOI: 10.1126/sciadv.1602883
|View full text |Cite
|
Sign up to set email alerts
|

Compliant substratum guides endothelial commitment from human pluripotent stem cells

Abstract: Surface stiffness during the early stages of stem cell differentiation affects vascular fate under chemically defined conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…5D): In this system, we observed four different types of domains; an edge of a pattern (black); the region of increased density toward the edge of a pattern-an annulus in the case of a circle (purple), the center of a pattern (yellow), and a region of increased density toward the edge of patterns with corners-and thus two neighboring edges-subjected to higher tension deeper into the center of the pattern (red). In a previous study, we tracked other mesodermal markers along our differentiation scheme, showing the temporal expression of markers including KDR, GATA-2, MESP-1, and SNAIL (26). We view the current study as a robust computational foundation to explore the temporal/spatial expression of these markers in the context of cytoskeletal tension, allowing more insight into mechanical regulation of vascular specification.…”
Section: Svm Learning Elucidates the Roles Of Cytoskeletal Tension Anmentioning
confidence: 87%
See 2 more Smart Citations
“…5D): In this system, we observed four different types of domains; an edge of a pattern (black); the region of increased density toward the edge of a pattern-an annulus in the case of a circle (purple), the center of a pattern (yellow), and a region of increased density toward the edge of patterns with corners-and thus two neighboring edges-subjected to higher tension deeper into the center of the pattern (red). In a previous study, we tracked other mesodermal markers along our differentiation scheme, showing the temporal expression of markers including KDR, GATA-2, MESP-1, and SNAIL (26). We view the current study as a robust computational foundation to explore the temporal/spatial expression of these markers in the context of cytoskeletal tension, allowing more insight into mechanical regulation of vascular specification.…”
Section: Svm Learning Elucidates the Roles Of Cytoskeletal Tension Anmentioning
confidence: 87%
“…After 48 h of culture, cells were fixed for immunofluorescence staining. To induce EVC specification, seeded micropatterns were cultured in Diff Media that on day 6 was switched to EC Diff Media (15,22,23,26). Cells cultured on micropatterned surfaces were fixed and stained (SI Appendix, Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a scaffold material, PDMS can be modified to contain chemical cues, including sites for cell adhesion. The mechanical properties of PDMS are easily manipulated and thus these scaffolds have been used to determine how mechanical properties of the microenvironment influence stem cell differentiation [200,253]. Another interesting tissue engineering application requires the incorporation of PDMS microspheres in stem cell aggregates.…”
Section: Polydimethylsiloxane (Pdms)mentioning
confidence: 99%
“…It is also known that hydrodynamic shear stress promotes the conversion of primary patient epithelial tumor cells into specific cancer stem-like cells [34]. Smith et al found that the mechanical context of the differentiation niche can drive endothelial cell identity from human-induced pluripotent stem cells, showing that stiffness drives mesodermal differentiation, leading to endothelial commitment [35]. Thus, microenvironments help specify stem cell lineages, although it may be difficult to decouple the influence of mechanical interactions and surface topography and stiffness from biochemical effects [12,35].…”
Section: Introductionmentioning
confidence: 99%